Households’ Involvement in Monitoring and Evaluation Decision-Making and Performance of Tanzania Conditional Cash Transfer Project - Bernard Katerengabo; Christopher Gakuu; Harriet Kidombo (European Scientific Journal, ESJ, 2022)
Poverty is one of the challenges affecting developing countries. In the efforts to curb this problem, Tanzania has been implementing a Conditional Cash Transfer project for reducing the poverty reduction rate among households that were identified to be extremely poor. Therefore, this study assessed the extent to which households’ involvement in Monitoring and Evaluation decision-making influenced the performance of the Tanzania Conditional Cash Transfer Project. Descriptive cross-sectional and correlational research designs were used, supported by a pragmatic paradigm. By using Yamane’s (1967) formula, a sample size of 400 respondents was obtained from a target population of 61,240 households. Data were collected through administered questionnaires, key in-depth interviews, and focus group discussions. The findings established a significant influence between households’ involvement in Monitoring and Evaluation decision-making (t=4.970, p-value=0.000) on the performance of the Tanzania Conditional Cash Transfer Project. It was concluded that households’ involvement in Monitoring and Evaluation decision-making played a significant role in the performance of the Tanzania Conditional Cash Transfer Project. Therefore, it was recommended that implementers of the project were required to establish the section in the M&E document that incorporates the involvement of households at the decision-making levels as a catalyst for influencing the performance of the Tanzania Conditional Cash Transfer Project.